Status of Hard and Soft HR Approaches: Evidence from Workplaces of Nepal (The Batuk, 2020)
Two of the most widely adopted approaches to HR are the hard and soft approaches. These concentrate on opposing views of human existence and methods of techniques for managerial power. In this regard, in the context of Nepalese workplaces, this paper aims to analyze hard and soft HR approaches. For the empirical study, a total of 375questionnaires (15 for each company) were distributed using non-probability sampling to the employees of 25 companies listed on the Nepal Stock Exchange. Among them, 247employees replied to questionnaires (representing 65.87 percent). A self-developed fourpointLikert-like scale has been used. The findings suggest that compensation is the highest priority of all companies as the main component of the Hard HR approach, while human resource planning receives less priority. The findings also suggest that the work environment is a top priority for all companies among the three dimensions (team cohesion, work environment, and communication flow) of the Soft HR approach, whereas employees and managers have a moderate level of communication and interaction in their companies. Team cohesion exists in their companies. Depending on the nature of the individual firm or organization, the approach to managing people canvary. To deal with employee relations issues, there should be a suitable representation of employees.